Disseminated septic arthritis caused by Streptococcus equi infection. Issue 6 (7th June 2020) - Mobeen, Khudaim Mohammed; Carter, Janine; Ahmed, Zaheer; Minton, Jane
Abstract : We describe a rare case of bloodstream infection and disseminated septic arthritis in a relatively fit and well 73-year-old retired farmer and gamekeeper, due to the zoonotic organism Streptococcus equi . The presence of the organism in multiple joints led to slow clinical response to treatment and was complicated by relapse of infection and lengthy disability. Source control was achieved with multiple joint washouts and spinal cord decompression. Following this, a 6-week course of intravenous antibiotics was required for complete clearance of infection. After a long period of rehabilitation, the patient made a good recovery. This case demonstrates that S. equi can cause life threatening and difficult to treat sepsis in humans and requires a high index of suspicion in people who have regular contact with equine species, cattle and unpasteurised milk.